Urgensi Menulis Bagi Mahasiswa: Refleksi atas Mata Kuliah Penulisan Naskah Dakwah - Muridan, Muridan (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2009)
Dakwah basically is changing one situation to a better situation. Besides by oral media, dakwah also deliveredwith written media. Nowadays, dakwah with written media is a must. There’s many media that can be used, several arebooks, journal, newspaper, magazine, tabloid, bulletin, etc. the better feature of written media are can be read many timesand also can reach many audience. Therefore, remembering importance of dakwah activity through written media, there’sa lesson especially for dakwah student, namely dakwah text writing lecture